2018
DOI: 10.1002/biot.201800081
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Secretion of a Glyco-Engineered Anti-CD20 scFv-Fc Antibody in Hairy Root Cultures

Abstract: Hairy root (HR) cultures represent an attractive platform for the production of heterologous proteins, due to the possibility of secreting the molecule of interest in the culture medium. The main limitation is the low accumulation yields of heterologous proteins. The aim of this study is to enhance the accumulation of a tumor-targeting antibody with a human-compatible glycosylation profile in HR culture medium. To this aim, the authors produce Nicotiana benthamiana HR cultures expressing the red fluorescent pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 38 publications
(58 reference statements)
1
11
0
Order By: Relevance
“…Almost certainly both bands derived from a proteolytic cleavage in the hinge region connecting constant domains (CH2-CH3) to scFv. This is not surprising since it was demonstrated that antibodies expressed in plants are particularly prone to proteolysis in the hinge region [20] and in a previous work, in which a scFvFc was expressed in HR of N. benthamiana, the purified antibody showed a similar degradation pattern [21].…”
Section: Discussionmentioning
confidence: 71%
“…Almost certainly both bands derived from a proteolytic cleavage in the hinge region connecting constant domains (CH2-CH3) to scFv. This is not surprising since it was demonstrated that antibodies expressed in plants are particularly prone to proteolysis in the hinge region [20] and in a previous work, in which a scFvFc was expressed in HR of N. benthamiana, the purified antibody showed a similar degradation pattern [21].…”
Section: Discussionmentioning
confidence: 71%
“…The biological activity studies with purified scFv-Fc exhibited an improved binding affinity compared to the non-engineered form of scFv and rituximab. Cytotoxicity induced through the antibody-dependent cell-mediated pathway and the complementary dependent pathway was strongly enhanced [18,126]. The data indicate that the major factor which prevents the use of plant system is the cost associated with the downstream purification of the recombinant protein rather than the post-translational changes associated with plant expression.…”
Section: Glycoengineering For the Mammalian Type Of Glycosylationmentioning
confidence: 93%
“…Addition of the plant growth regulator 2,4-D was found to be enhancing the secretion of recombinant antibodies about 28-fold to the culture vessels. The purified CD20 2B8-Fc effectively bound to the CD20 antigen on the surface of human Daudi cells [18]. Transient expression is favored when the protein is needed within a short span of time in a comparatively large quantity [53,93,94] and for the expression of proteins which have an adverse effect on the host cells when overexpressed [95].…”
Section: Transformation Methodologies Target Plants and Expression Omentioning
confidence: 99%
See 2 more Smart Citations